Comparing Component-Based and Occupation-Based Interventions of a Person with Visual Deficits' Performance. Issue 1 (2nd January 2021) - Gartz, Rachel; Dickerson, Anne; Radloff, Jennifer C.
Abstract: This study aimed to compare the effectiveness of component-based, occupation-based, and a combined intervention for visual-scanning to improve occupational performance. This exploratory case study used a 55-year-old female, seven years post-stroke with visual field deficits, who completed a component-based intervention ( Vision Coach ), an occupation-based intervention (IADL activities that incorporated scanning tasks), and a combined intervention. The Assessment of Motor and Process Skills (AMPS) was completed prior to and after each intervention. Participant's data was compared between interventions and AMPS standardization sample, with observable improvements in motor skills and process skills. Visual-scanning training as a compensatory method appears to be effective for chronic visual field deficits post-stroke, particularly using component-based and occupation-based interventions in combination.